Effective teaching strategies for teaching mathematics to young gifted English learners. (May 2023) - Yang, Jenny; Özbek, Gülnur; Liang, Shaoru; Cho, Seokhee
Project BRIDGE was launched as a response to the underrepresentation of English learners in gifted education. Through Project BRIDGE, high-ability English learners were able to access the same rigorous academic content as their native English-speaking peers. The present study compared intervention and comparison teachers' instructional behaviors in curriculum planning and delivery, accommodation in individual differences, problem solving, critical thinking strategies, creative thinking strategies, language strategies. The data on student-teacher interactions in second-grade math classes were collected through structured observation and analyzed quantitatively and qualitatively. The results showed that the intervention teacher was more effective than the comparison teacher in: 1) establishing high expectations for student performance; 2) implementing activities that promote critical and creative thinking; 3) engaging students in active classroom talk; and 4) providing supports for language development.